Adding an Internet-delivered Treatment to an Efficacious Treatment Package for Opioid Dependence - Christensen, Darren R. (J Consult Clin Psychol, 2014)
OBJECTIVE: To examine the benefit of adding an internet-delivered behavior therapy to a buprenorphine medication program and voucher-based motivational incentives. METHOD: A block-randomized, unblinded, parallel, 12-week treatment trial was conducted with 170 opioid-dependent adult patients (mean age 34.3 years; 54.1% male; 95.3% white). Participants received an internet-based community reinforcement approach intervention plus contingency management (CRA+) and buprenorphine, or contingency management alone (CM-alone) plus buprenorphine. The primary outcomes, measured over the course of treatment, were longest continuous abstinence, total abstinence, and days retained in treatment. RESULTS: Compared to those receiving CM-alone, CRA+ recipients exhibited on average 9.7 total days more of abstinence, 95% CI: (2.3, 17.2), and had a reduced hazard of dropping out of treatment, Hazard Ratio (HR)=0.47; 95% CI: (0.26, 0.85). Prior treatment for opioid dependence significantly moderated the additional improvement of CRA+ for longest continuous days of abstinence. CONCLUSIONS: These results provide further evidence that an internet-based CRA+ treatment is efficacious and adds clinical benefits to a contingency management/medication based program for opioid dependence.